Feasibility, Difficulties and Countermeasures of Mixed-age Education in Coastal Cities - Dai, Jiamei (Journal of Theory and Practice in Education and Innovation, 2025)
One of the basic concepts of mixed-age education is that a kindergarten class is similar to a warm family. In such a family, there are children of different ages who live together like brothers and sisters, playing and learning together. Since each child is a member of this family, they also have their own living space and preferences. Against the specific regional background of China's coastal cities, it is of great practical significance to conduct in-depth exploration into the implementation of mixed-age education. It is necessary for us to systematically analyze the advantages and disadvantages of mixed-age education as well as its feasibility in coastal areas. From the perspective of advantages, coastal areas are often relatively developed economically, with relatively rich educational resources. Parents generally have a relatively high level of education and are more receptive to advanced educational concepts, which provides a good material foundation and conceptual support for the implementation of mixed-age education. The advantages of mixed-age education, such as cultivating children's social communication skills, enhancing empathy, and promoting the complementarity of knowledge among different age groups, are also expected to be brought into fuller play here. In China's coastal cities, we will analyze the advantages and disadvantages of mixed-age education, its feasibility in coastal areas, as well as the drawbacks in its application in coastal areas and the corresponding optimization methods. Combining the characteristics of the Minnan region, we will organically integrate them into the mixed-age education in kindergartens so that they can promote and grow with each other. We will analyze the factors of families, society and kindergartens, and strive to expand and deepen the reform of mixed-age education.